To solve this system of equations, we are looking for the values of x and y that satisfy both equations simultaneously. Since we have an equation for y in terms of x in both equations, we can set the two expressions for y equal to each other:
4x - 9 = 2x + 9
Now, we can solve for x:
4x - 2x = 9 + 9
2x = 18
x = 9
Now that we have found the value of x, we can substitute it back into either of the equations to find the value of y. Let's use the first equation y = 4x - 9:
y = 4(9) - 9
y = 36 - 9
y = 27
Therefore, the solution to the system of equations is x = 9 and y = 27.
solve the system of equations:
y = 4x - 9
y = 2x + 9
1 answer